FORMATION OF AN ECONOMIC MECHANISM FOR INCREASING THE COMPETITIVENESS OF AN ENTERPRISE BASED ON THE MARKETING CONCEPT - KUTLINA, Iryna; HERLІAN Yakiv (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the study is to develop and theoretically substantiate an economic mechanism for ensuring the competitiveness of an enterprise based on the marketing concept, which involves a comprehensive coordination of conceptual, resource-operational and economic components. The need for a systemic approach to the formation of an enterprise’s competitive advantages is substantiated by integrating various subsystems and applying modern marketing tools that contribute to the effective use of internal resources and adaptation to changes in the market environment. The methodological basis of the study is made up of general scientific methods of analysis and synthesis, systematization, comparison and generalization of existing scientific approaches, as well as structural and logical modeling of key elements of the economic mechanism. In the process of the study, a classification of interpretations of the concept of "economic mechanism" was carried out, the features of its functioning in market relations were determined, and an own scheme for the formation of an economic mechanism for the competitiveness of an enterprise based on marketing was proposed. The results of the study provide for a detailed description of the functions of the managing and managed subsystems, a description of the procedures for goal setting, resource provision and monitoring of market positions. It is proven that the effectiveness of the implementation of the developed mechanism depends on the balance of intellectual, financial and material resources of the enterprise and the ability to provide long-term competitive advantages by minimizing costs and strengthening interaction with consumers. The practical value of the study lies in the possibility of using the proposed mechanism as a methodological tool to increase the competitiveness of enterprises in a dynamic market environment. The proposed recommendations can be adapted to the specifics of the activities of enterprises in the tourism industry and other service sectors that operate on the principles of marketing orientation. It is concluded that further research aimed at empirically verifying the effectiveness of the proposed economic mechanism and its integration into the development strategies of enterprises in various industries is appropriate. The results obtained allow us to assert that a comprehensive economic mechanism for the formation of competitiveness ensures the sustainable development of the enterprise, strengthens its market position and contributes to increasing economic efficiency.